Non-standard employment in Kazakhstan as an object of structural modeling - Atabayeva, A.; Pritvorova, T.; Syzdykova, E.; Lambekova, A. (Economic Annals-XXI, 2020)
Phenomenon of employment transformation in the modern economy is the subject of active discussions. Identification of factors influencing its development and the construction of a model of «new» (non-standard) employment are particularly topical. Based on the results of previous studies, we have identified both personal (human capital, education) and external factors (digitalization, social protection), put them forward and tested hypotheses about their impact on non-standard employment. We have constructed a structural model that reflects both the factors affecting non-standard employment, and the socio-economic parameters of society affected by non-standard employment (income and social inequality). We have assessed reliability and internal consistency of the model as well. Based on the results obtained, we have determined the degree of studied factors’ influence on non-standard employment in Kazakhstan. For the research, we used methods of online polling, modeling using structural equations (SEM) of SmartPLS software. Based on the results of the PLS analysis, we have identified two main issues of non-standard employment in Kazakhstan: a low level of social protection and inability to accumulate human capital of employees. Obtained determination coefficients (0.8, 0.5, and 0.58) indicate that the unstable nature of non-standard employment (instability, low wages) leads to an increase in poverty and social inequality. We have proposed measures to regulate these issues by improving legislation on social insurance for non-standardly employed citizens, and taking active measures to promote employment, including a state employment program.
Keywords: Non-standard Employment; Remote Work; Salary; Income; Human Capital; Employee; Social Protection; Social Insurance; Digitalization; Education